Capacity Building of Principals and Islamic Education Teachers on SPMI Implementation in North Lampung - Supriyanti, Supriyanti; Supriadi Wijaya; Siti Rukayat; Sri Setiyoningsih; Adil Muhammad Toyib (LP2M INSURI Ponorogo, 2025)
This mentoring program aimed to enhance principals’ and teachers’ understanding and practical skills in implementing the Internal Quality Assurance System (SPMI) in Islamic Religious Education (PAI) learning, thereby fostering a quality culture grounded in Islamic values. The program was motivated by the low level of SPMI understanding and implementation in schools in North Lampung Regency, where PAI learning had largely been administrative and had not sufficiently addressed students’ character and value development. The activity was designed as a participatory, mentoring-based community service program involving 10 school principals and 25 PAI teachers from six public secondary schools, and was conducted over three months. The mentoring was implemented through four stages: socialization of SPMI and the PPEPP cycle, technical training on quality-based learning documents, field mentoring during classroom implementation, and monitoring and evaluation. The results indicate a significant improvement in participants’ understanding of SPMI and the PPEPP cycle. Teachers were able to develop value-based learning documents, apply reflective learning strategies, and implement character-oriented evaluation, while principals demonstrated stronger leadership as drivers of school quality culture. This mentoring also strengthened collaboration among principals, teachers, and supervisors in implementing an integrative and contextual SPMI. In the long term, this program contributes to the development of a sustainable quality assurance system for Islamic education. It offers a replicable mentoring model for other regions with similar educational contexts